Environmental assessment of contaminants in a downstream area of a landfill - Koutsopoulou, E.; Katsanou, K.; Papoulis, D.; Zagana, E.; Tsolis- Katagas, P. (Bulletin of the Geological Society of Greece, 2013)
Therefore, the evaluation of environmental risks associated with a landfill and the effect of landfill surface runoff was investigated. Soil samples were collected in the downstream area of the waste disposal site and their mineralogy was studied. An appraisal of the heavy metal contamination in the area was attempted. Top layers of sediments seem to interact with chemically modified surface runoff waters from the landfill. Heavy metals such as As and Pb were in significant concentrations in the sediments within a distance of 200 m from the site. Anions such as chloride, sulphate and phosphate adsorbed on clay minerals suggest the interaction of sediments with surface runoff from the waste disposal site. Inorganic parameters NH4 + and NO2 - in surface water samples are above or slightly below the guidelines recommended by EE and WHO. The results indicated that environmental monitoring of the landfill is considered essential.